2015
DOI: 10.17957/ijab/15.0023
|View full text |Cite
|
Sign up to set email alerts
|

Poly-𝛽-hydroxy butyrate Depolymerase from Streptomyces lydicus MM10, Isolated from Wastewater Sample

Abstract: To cite this paper: Aly, M.M., S. AbstractPlastics are an integral part in our daily life activities and it is difficult to conceive how we could function without them. Burning or chemical treatments of these plastic materials destroys the environment and have many dangerous effects on, water air and human health. Thus, other sources of plastic (biodegradable plastic) must be introduced. Under unfavorable growth conditions Poly ß-hydroxybutyrate (PHB) is accumulated intracellular by many bacteria and the prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…However, yield was low at initial pH of 5.0 (0.62 U/mL) and 7.5 (0.28 U/mL). Likewise, Magda et al (2015) observed significant effect on the P(3HB) depolymerase production from Streptomyces lydicus MM10 by manipulating the initial pH. They described the production of P(3HB) depolymerase as high at pH 7.0, but low when initial pH was 10.…”
Section: Resultsmentioning
confidence: 96%
“…However, yield was low at initial pH of 5.0 (0.62 U/mL) and 7.5 (0.28 U/mL). Likewise, Magda et al (2015) observed significant effect on the P(3HB) depolymerase production from Streptomyces lydicus MM10 by manipulating the initial pH. They described the production of P(3HB) depolymerase as high at pH 7.0, but low when initial pH was 10.…”
Section: Resultsmentioning
confidence: 96%
“…Statistical analysis was performed with GraphPad Prim 5. The statistical significance was calculated and used to test the effects of UV radiation pre-treatment and the addition of yeast extract to the culture medium, using a two-tailed paired t-test with a 95% confidence interval [37,112].…”
Section: Discussionmentioning
confidence: 99%